Comparison of patients undergoing general anesthesia or ultrasonography-guided interscalene block in shoulder surgery in terms of postoperative analgesia: A retrospective study (Annals of Medical Research, 2025)
Aim: We aimed to evaluate the pain scores with visual analog scale and compare opioid consumption in the early postoperative period in cases where single-shote interscalene brachial plexus block and general anesthesia or general anesthesia alone have been applied for arthroscopic shoulder surgery.Materials and Methods: Seventy-one patients, aged 18-65, who had undergone elective arthroscopic shoulder surgery were included in this study. Participants were allocated to one of two groups: the General Anesthesia (GA) group (n=36) or the Interscalene Block and General Anesthesia (ISBPB+GA) group (n=35). The severity of postoperative pain was evaluated using Visual Analog Scale (VAS) scores.Results: The VAS scores and analgesic requirements of patients in the ISBPB+GA group were significantly lower than GA group. Although the duration of operation was shorter in the ISBPB+GA group (87.37±17.65 min), it did not reach statistical significance (p˃0.05). Surgeon and patient satisfaction scores were higher in the ISBPB+GA group compared to patients who underwent GA alone.Conclusion: The cases that underwent ISBPB+GA had notably lower pain scores and decreased additional analgesic consumption in the postoperative period. We believe that this anesthesia technique provides a more comfortable recovery process in patients undergoing shoulder surgery and can be safely utilized by experienced anesthesiologists.
Keywords: Interscalene block; Shoulder surgery; Postoperative analgesia